Stress in borderline personality disorder: A review of the particular experience from a micro-phenomenological perspective - Pacheco, Cristóbal (2021)
The development of an approach to the experience of stress in people with borderline personality disorder is an important challenge, based on the selection of a methodology that allows capturing the chronology and characteristics of the particular experience that occurs during the development of a stressful situation. For the present research, microphenomenological interviews with 3 participants presenting a borderline personality disorder were considered, in order to favor the articulation of a structure of the lived experience, organized from the prereflective perspective. The theoretical and methodological assumptions considered are based on the approaches of Pierre Vermesch (1994) and their respective adaptation to the clinical context developed by Petitmengin (2006, 2007). The microphenomenological interview, starts from the assumption that much of the experience, goes unnoticed in our immediate awareness, the subjective experience of something we feel, smell or perceive or experience, cannot be immediately accessed from our reflective awareness or the development of verbal descriptions (Petitmengin, Remillieux y Valenzuela-Moguillansky, 2019). The present research engages the development of an organized view of the linkage to a stressful situation, from a diachronic and synchronic understanding, developing elements that provide clarity and possible new research challenges in the present topic. As results, indicators associated with the presence of physical, emotional and sensory alterations have been obtained, which shows that the experience of stress in this group is associated with a holistic experience that integrally encompasses different spheres of individual development.